1996
DOI: 10.3989/egeol.96521-2251
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: El salar de Llamará es un sistema salino que se mantiene activo gracias a su especial situación geomorfológica y a las características climáticas de la zona donde se localiza, conocida como «Norte Grande de Chile». Las acumulaciones superficiales de agua constituyen verdaderas salmueras de tipo clorurado-sódico y pH aproximadamente neutro. Por otra parte, la composición de los depósitos bajo lámina de agua del salar es fundamentalmente yesífera.El desmuestre realizado sobre el sistema a lo largo de dos campaña… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Garcés et al report a radial density gradient (from inside to outside), most likely due to differences in the flow regime within the area, with the data in Tables S2 and S4 corresponding to a situation where both recharge and drain were larger than in the previous study, leading to more diluted brines overall (as observed comparing both data sets).…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…Garcés et al report a radial density gradient (from inside to outside), most likely due to differences in the flow regime within the area, with the data in Tables S2 and S4 corresponding to a situation where both recharge and drain were larger than in the previous study, leading to more diluted brines overall (as observed comparing both data sets).…”
Section: Resultsmentioning
confidence: 53%
“…No top/bottom gradients have been taken into account previously for diagenesis purposes but are clearly observed in our data taken in situ. This result is relevant for studies, such as isotopic analysis, in which the homogeneity or stratification of the waters play a relevant role.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations